Measurement of jet production in deep inelastic scattering and NNLO determination of the strong coupling at ZEUS - Abt, Iris; Aggarwal, R.; Aushev, V.; Behnke, O.; Bertolin, A.; Bloch, I.; Brock, I.; Brook, N. H.; Brugnera, R.; Bruni, A.; Bussey, P. J.; Caldwell, A.; et al. (The European physical journal. C, Particles and fields, 2023)
A new measurement of inclusive-jet cross sections in the Breit frame in neutral current deep inelastic scattering using the ZEUS detector at the HERA collider is presented. The data were taken in the years 2004-2007 at a centre-of-mass energy of 318 GeV and correspond to an integrated luminosity of 347 pb(-1). The jets were reconstructed using the k(t)-algorithm in the Breit reference frame. They have been measured as a function of the squared momentum transfer, Q(2), and the transverse momentum of the jets in the Breit frame, p(perpendicular to,Breit). The measured jet cross sections are compared to previous measurements and to perturbative QCD predictions. The measurement has been used in a next-to-next-to-leading-order QCD analysis to perform a simultaneous determination of parton distribution functions of the proton and the strong coupling, resulting in a value of alpha(s) (M-Z(2)) = 0.1142 +/- 0.0017 (experimental/fit)(-0.0007)(+0.0006) (model/parameterisation)(-0.0004)(+0.0006) (scale), whose accuracy is improved compared to similarmeasurements. In addition, the running of the strong coupling is demonstrated using data obtained at different scales.
Gesehen am 28.02.2025